Can Portek (Portable Engklek) be a Solution to Teach Vocabulary to English Young Learners? - Fitri Yulianti (ETERNAL (English Teaching Journal), 2017)
The main goal of this article is to find out whether or not PORTEK be a solution to teach vocabulary to English young learners.  Previously, there were some studies conducted to prove the effectiveness of PORTEK as English teaching media, especially in teaching vocabulary.  But the writer assumed that she needed to conduct one more study to conclude her previous findings.  She used library research with qualitative data to answer the research question.  The data from her previous studies were used as the primary data.  The result of her study was showed in tables to ease the readers get the conclusion.  At the end, it can be concluded that PORTEK can be a solution to teach vocabulary to English young learners.